2020
DOI: 10.1002/alz.041080
|View full text |Cite
|
Sign up to set email alerts
|

A novel MRI contrast agent for identifying hyperphosphorylative neurons as a marker of future tau pathology

Abstract: Background Hyperphosphorylated tau (pTau) is a precursor to tau tangle formation in Alzheimer's disease (AD). We have identified aptamers that bind to specific cell membrane receptors of human neuronal cells that are hyperphosphorylating tau. In this work, we built a novel targeted nanoparticle magnetic resonance imaging (MRI) contrast agent, TauX, that binds such neurons, and tested its efficacy in vivo in the P301S mouse model of tau pathology. Method DNA aptamers preferentially binding on the cell membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Notably, this product demonstrated enhancing the MRI signal in the transgenic PS19 mice line, 4 to 6 months before the subjects showed tauopathy symptoms. As a further note, studies employing artificial intelligence (AI) techniques to analyze MRI-image-related data and other readily available information for predicting the clinical status of patients with neurodegenerative diseases have very recently been proposed and applied for amyloids [150][151][152][153]. An example of this comes from a very recent study by Lew and colleagues [154], who reported the development and application of a deep learning approach able to predict the PETdetermined amyloid-tau-neurodegeneration (ATN) biomarker status from MRI and other patient-related data reported in the Alzheimer's Disease Neuroimaging Initiative (ADNI) database (www.adni-info.org, accessed on 29 November 2023).…”
Section: Tau Probesmentioning
confidence: 99%
“…Notably, this product demonstrated enhancing the MRI signal in the transgenic PS19 mice line, 4 to 6 months before the subjects showed tauopathy symptoms. As a further note, studies employing artificial intelligence (AI) techniques to analyze MRI-image-related data and other readily available information for predicting the clinical status of patients with neurodegenerative diseases have very recently been proposed and applied for amyloids [150][151][152][153]. An example of this comes from a very recent study by Lew and colleagues [154], who reported the development and application of a deep learning approach able to predict the PETdetermined amyloid-tau-neurodegeneration (ATN) biomarker status from MRI and other patient-related data reported in the Alzheimer's Disease Neuroimaging Initiative (ADNI) database (www.adni-info.org, accessed on 29 November 2023).…”
Section: Tau Probesmentioning
confidence: 99%
“…The detection was verified by colocalization with anti-phosphorylated tau antibody AT8-positive tau deposits. Badachhape et al (2020) and Parekh et al (2021) demonstrated tau imaging using the DNA aptamer-targeted liposomal-Gd nanoparticle TauX, which binds to the surface of hyperphosphorylative cells, for T 1 -weighted spin echo MRI in PS19 mice ( Figure 1A ). Increased TauX-enhanced post-contrast MR signal enhancement was detected at 2 months of age in PS19 mice (which showed tauopathy 4–6 months later) compared with wild-type mice, with an accuracy of approximately 0.8 ( Figure 1B ).…”
Section: Tau Imagingmentioning
confidence: 99%
“…Sensitivity describes the true positive rate for transgenic mice given TauX, while specificity is the true negative rate for wild-type mice given TauX and transgenic mice receiving untargeted gadolinium nanoparticle contrast. Reproduced from Badachhape et al (2020) with permission from Elsevier. (C) Functional connectivity matrices of transgenic rTg4510 and wild-type mice at baseline and after 8weeks of treatment with doxycycline.…”
Section: Tau Imagingmentioning
confidence: 99%
“…(1) Gadolinium (Gd) based: Gd-diethylenetriamine pentaacetate (DTPA)-Aβ1-40, Gd-DTPA-K6Aβ1-30, cyanine-conjugated Gd (III) complex, Gd-pF(ab’)24, and liposomal macrocyclic Gd-ADx-001 [ 34 , 35 , 36 , 37 , 38 , 39 ] ( Figure 1 f).…”
Section: Aβ Imagingmentioning
confidence: 99%